2021
DOI: 10.3390/polym13203594
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Electrospun Folic Acid/Hybrid Fibers: In Vitro Controlled Release Study and Cytocompatibility Assays

Abstract: The fabrication of skin-care products with therapeutic properties has been significant for human health trends. In this study, we developed efficient hydrophilic composite nanofibers (NFs) loaded with the folic acid (FA) by electrospinning and electrospraying processes for tissue engineering or wound healing cosmetic applications. The morphological, chemical and thermal characteristics, in vitro release properties, and cytocompatibility of the resulting composite fibers with the same amount of folic acid were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 61 publications
(66 reference statements)
1
15
0
Order By: Relevance
“…The cell viability assay of optimized microsphere (F 6 ) was performed by (3‐[4,5‐dimethyl thiozol‐2yl]‐2,5 diphenyltetrazolium bromide) MTT assay on HT29 cell line 39,40 . Here only the viable cells were reduced MTT to the formazan crystals.…”
Section: Methodsmentioning
confidence: 99%
“…The cell viability assay of optimized microsphere (F 6 ) was performed by (3‐[4,5‐dimethyl thiozol‐2yl]‐2,5 diphenyltetrazolium bromide) MTT assay on HT29 cell line 39,40 . Here only the viable cells were reduced MTT to the formazan crystals.…”
Section: Methodsmentioning
confidence: 99%
“…Four mathematic models, such as first-order kinetic ( ), Higuchi ( ), Rigter–Peppas ( ), and zero-order kinetic ( ) model, were used to further process drug data [ 37 , 38 , 39 , 40 ]. where , , and are the initial drug amounts; k is the kinetic constant; n is the drug diffusion coefficient; and t is the time required for drug release.…”
Section: Characteristicsmentioning
confidence: 99%
“…The fabrication of electrospun PVA/ZnO nanowebs from precursor PVA/ZnAc nanowebs have been studied for different purposes such as biomedical ( Jamnongkan et al, 2018 ), high-tech ( Wu et al, 2006 ) applications, and drug delivery ( Anero et al, 2021 ). The applications of functional electrospun PVA in transdermal drug delivery ( Parin et al, 2021a ), as bioactive fibers ( Parin et al, 2021b ), and in electronic skin textile ( Wang et al, 2021 ) have also been documented. Previous studies that explored the production of PVA/ZnO from precursor PVA/zinc acetate reported varying parameters specific for purpose.…”
Section: Introductionmentioning
confidence: 99%